Involvement of the Board in Strategic Control: the Role of Structure - Shahram Khalil Nejad; Taha Nejad Falatouri; Esmaeil Hassanpour (مطالعات مدیریت راهبردی, 2015)
Organizations achieve sustainable success through permanent and proactive construction of the context. The strategic control, as a factor of strategic management, is a mechanism for realizing this flexibility. Moreover, with respecting to the growing separation of ownership and management, the board role in strategic orientation of organization becomes increasingly more important. Therefore, the role of the board in strategic control, that has been almost ignored practically and theoretically, is undeniable. The paper explains the relationship between structural dimension of board and its contribution in strategic control. For this purpose, dimensions of strategic control and board of directors are identified. Then, the role of the structural dimension of the board in strategic control is analyzed, and the model is created and tested. The study finds that the diversity, the size, the managerial duality and the ratio of internal members have meaningful role in proactive involvement of the board in strategic control.